Conclusion - Catherine Vincent (Reti Medievali Rivista, 2016)
This conclusion first points out that the principal merit of the dossier is to make people aware of the diversity of these phenomena, but also of their complexity: what is behind the concept of replication? A place did not need to be ad formam to fulfill the mission that was assigned to it, and identical reproduction was probably not what commissioners and users were looking for. A range of items were mobilized to animate the “replicas” in the context of religious drama, or even directly in the liturgy, thus actualizing a process that was not solely commemorative. In conclusion, the dossier emphasizes the paradox inherent to the spatial dimension of the replication process, both breaking with the uniqueness of the sacred place and considering it accessible almost everywhere the faithful are ready to implement and live it through this continuos development. The fondament idea – as the Church Fathers affirm – is that the true temple is within man.